Hybrid endovascular treatment of an aberrant right subclavian artery with Kommerell aneurysm. (December 2014) - Lamb, KM; Moudgill, N; Whisenhunt, AK; Ayad, M; Abai, B; Salvatore, D; DiMuzio, PJ
Aberrant right subclavian artery is a rare anatomical finding of abnormal embryologic development of the dorsal aorta and right subclavian artery. An associated aortic outpouching, or Kommerell diverticulum, may develop at the origin of the aberrant right subclavian artery. Given historically high rates of aneurysm rupture and mortality, early repair is indicated. Successful aneurysm exclusion can be accomplished with thoracic endovascular stent grafting following open carotid-subclavian bypass, maintaining upper extremities perfusion. Such hybrid techniques offer a decrease in mortality and complication rates. Herein, we describe a successful repair of a symptomatic (dysphagia, weight loss) aberrant right subclavian artery with Kommerell diverticulum using this hybrid open-endovascular approach.